(untitled) (Bangladesh Journal of Botany, 2008)
Chlorophytum nepalense (Lindley) Baker, a perennial herb, belonging to the family Liliaceae has been described and illustrated as a new genus and species record for Bangladesh. Key words: Chlorophytum nepalense, New record, Bangladesh doi:10.3329/bjb.v37i2.1730 Bangladesh J. Bot. 37(2): 193-194, 2008 (December)